Income tax preparation system / Lee Hong Yin - Lee, Hong Yin (2002)
The current income tax assessment system whereby income tax is assessed on the income earned in the preceding year and is assessed by the Inland Revenue Board (Jabatan Hasil Dalam Negeri) will be changed to a Self Assessment System. Self Assessment is the manner by which a taxpayer works out and pays his own income tax. It is not a new tax but a system whereby the taxpayer is given the responsibility to compute his own tax liability. Self Assessment is a total process change from the previous formal assessment system. Under the formal system, taxpayers are required to declare their income in the Return Form, submit the Return Form to the Inland Revenue Board (IRB) and IRB will then raise the assessment. The notice of assessment is sent to the taxpayer and based on the tax raised in the Notice of Assessment, payment must be made accordingly. Therefore this project will produced an online Income Tax Preparation System for the tax payers to ease their burden and duty to the country.